Elaboration of Integration Strategies for Urban Marginalized Communities : Integrated Summary - World Bank (World Bank, Washington, DC, 2016)
For the 2014-2020 programming period, the Government of Romania (GoR) is considering a new approach proposed by the European Commission (EC) - Community-Led Local Development (CLLD). CLLD comes with a unique set of challenges. These include making sure that the process is truly inclusive, community-led, transparent, and focused on peer-to-peer learning across communities and other stakeholders. The GoR should carefully weigh potential benefits and risks of applying the CLLD approach and put in place an adequate implementation framework with sufficient risk mitigating measures before pursuing CLLD. The World Bank undertook this advisory activity to help the GoR put in place an implementation framework for CLLD in Romania, should it want to go ahead with this approach. It includes a proposed definition of urban marginalized communities, the population group that the GoR wants to target by CLLD. The definition is based on a review of the Romanian literature on (urban) marginalization and on qualitative research in ten cities. It also includes guidelines for CLLD implementation based on EC guidance, extensive field work, and an assessment of lessons learned of similar programs in Romania and elsewhere. Moreover, detailed maps of urban marginalized areas across Romania are presented. These are based on a set of indicators, for which data are available in the 2011 Population and Housing Census dataset. Six conceptual pilots have been prepared that are based on simulated CLLD processes and can serve as examples for municipalities/NGOs that could be applying for EU funding through the CLLD approach, during the 2014-2020 programming period. This extensive summary brochure presents a synopsis of all findings and messages across the outputs produced under this activity.